FACTOR ANALYSIS ON PET LOVERS INTENTION TO UTILIZE TELEMEDICINE APPLICATION FOR PETS THROUGH INTEGRATION MODEL UTAUT2 AND TPB - Fredlina Margaret; Firdaus Alamsjah; Anak Agung Ngurah Perwira Redi Perwira Redi (Universitas Islam Balitar, 2023)
The purpose of this study were to determine the factors that influence pet owners' intentions to use telemedicine applications for their pets. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT2) and the Theory of Planned Behavior (TPB), in order to gather information, a survey of pet owners in Indonesia a random sampling method was used. Respondents filled out a total of 400 questionnaires, which were gathered. Using Smart Partial Least Squares (PLS) version 3.0, an analysis was done on the data that was collected. Positive factors included performance and effort expectations, attitude toward use, facilitating conditions, subjective norm, and intention to use. According to the findings, future development strategies should prioritize factors that positively influence pet owners' intentions to use telemedicine apps for pets.